(untitled) (Damu Journal of Sport Sciences, 2024)
The use of special skill exercises based on a model is the criterion for developing the skill by measuring some kinematic variables of players while performing the skill and trying to reach the ideal performance. The research problem was that most trainers in training centers do not give enough attention to mechanics, which in turn helps improve the skill performance of players. Therefore, the researchers decided to study this topic to address it and find effective ways to raise the level of skill performance by preparing special exercises developed by the researchers. The aim of the research is to identify the effect of using special exercises according to a model in some of the verbal variables of the research sample. The researchers used the experimental method to suit the nature of the problem. The sample was determined by the youth and sports team for table tennis in Najaf Governorate, and their number reached 24 players. Pre- and post-tests were conducted in addition to processing them statistically. The researchers concluded that there were significant differences in the values ​​of the kinematic variables of the table tennis serve skill.